TEACHER’S USE OF MOTIVATIONAL STRATEGIES IN SPEAKING CLASSES FOR SECOND YEAR MAINSTREAM ELT STUDENTS AT FELTE-ULIS IN CORRELATION WITH TEACHING EXPRIENCE - Nguyen, Thi Lien Huong (2020)
The topic of teachers’ motivational teaching practice has been receiving increasing attention during the past few years, with several researches investigating on motivational strategies applied by teachers in classrooms, as well as their perceived effectiveness on students’ motivated behaviours. However, hardly any study has touched upon the correlation between teachers’ use of motivational strategies and their teaching experience. This is the gap the researcher would like to bridge with her attempt in the field. In order to achieve this aims, the researcher employ questionnaires, interviews and classroom observation as data collection instruments. The result from the analysis of field data shows that there is significant differences in the use of motivational strategies among junior and senior teachers, which can be behaviourally explained; for examples young teachers often tend to display their energetic sides, thus pay more attention to activities that encourage competition; while more experienced teachers seem to be more into meaningful and challenging activities that promote students’ individual interests, such as personalization, element of interest, creativity and fantasy, etc.